(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Future School of Comprehensive Wellbeing (SchoolWell) is a multidisciplinary consortium funded by the Finnish Strategic Research Council. Our essential goal is to influence on the heart of the Finnish comprehensive school, the everyday pedagogical action, and to create solutions to support comprehensive wellbeing and learning, together with the children, youth, and the adults working with them. Expanding opportunities for physical activity throughout the school day is a central element of the SchoolWell intervention. Project Description: Prior to the SchoolWell intervention, 10 systematic literature reviews were conducted to gather insights on effective strategies for promoting students’ comprehensive wellbeing within the school context. This information, along with a co-design process involving teachers and students, was used to develop the SchoolWell intervention programme. Our intervention design is a cluster-randomised, hybrid Type 2 trial, in which we simultaneously evaluate both the effectiveness and implementation outcomes of the SchoolWell intervention. The SchoolWell intervention is targeted at Grade 5 and 8 students (n = 1,800) in the Finnish teacher training schools. Schools assigned to the intervention group will implement weekly SchoolWell activities throughout the entire school year as part of the regular curriculum. These activities encompass socio-pedagogical approaches – methods of teaching, learning, and studying – that support students’ mental, social, and physical wellbeing, while remaining aligned with standard curriculum goals. In addition to standard training, intervention schools will receive six implementation support strategies designed to enhance the knowledge and skills required for effective delivery. We will promote physical activity during the school day through quality physical education, active classroom practices, and by encouraging active recess. Upon completion of the SchoolWell intervention, we will disseminate best practices to all Finnish schools via the Finnish National Agency for Education. Conclusion: We will contribute to the next Finnish core curriculum by developing socio-pedagogical practices that enhance students’ comprehensive wellbeing in schools. All Finnish schools will have the opportunity to adopt SchoolWell practices to promote physical activity during the school day.